Análisis sedimentológico de facies de rampa externa: la Formación Agrio (Cretácico inferior), en el sector central de la Cuenca Neuquina, Argentina - Comerio, Marcos (2017)
Microfacies of distal marine deposits of the Lower Cretaceous Agrio Formation – Pilmatué and Agua de la Mula members – in the Neuquén basin has been analyzed taken into account field data, whole-rock phase-minerals and clay mineralogy with X-ray diffraction, organic components and optical and electron microscopy. Depositional and diagenetic fabrics are compared for the lowermost part of both members. Two facies associations were distinguished that correspond to two depositional settings: distal outer ramp (FA-1); and, proximal outer ramp (FA-2). FA-1 is composed of sediments mainly deposited by suspension settling with calcareous microfossils partially preserved as fecal pellets and organo-minerallic aggregates related to high bioproductivity in the water column. Conversely, FA-2 is dominated by extrabasinal components with illite-rich clay- to silt-si - zed particle aggregates. Storm-influenced processes have a main role in sediment transportation and accumulation as well as controlling oxygenation pulses of the bottom waters. In addition, burial diagenesis was evaluated taking into account thermal maturity of organics together with diagenetic textures such as growth of authigenic minerals and mechanical and chemical compaction features. Due to clay mineral assemblages are mainly detrital in origin the possible effects of burial diagenesis on them cannot be directly evaluated.